Potency of freshwater fishes in Aceh waters as a basis for aquaculture development program [Potensi ikan air tawar di Aceh sebagai dasar untuk pengembangan budi daya] - Z. A. Muchlisin (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
The development of aquaculture industry of Aceh Province should be based on local potency of indigenous species; however adequate information on the economic status of these freshwater fishes is crucially needed to support this activity. Hence, the objective of the present study was to evaluate the potency of the freshwater fishes which found in Aceh waters as a basic for aquaculture and conservation program. Explorative sampling was conducted from January 2008 to July 2012 in seventeen locations of Aceh Province. A total of 114 species of freshwater fishes were document-ted during the survey, of which 84 species were true freshwater fishes and the rest species were estuarine fishes. Among the freshwater fishes about 40were utilized for consumption, of these 14 species were of high economic value and they have potential as fish target for aquaculture, while at least 21 species displayed potential for the ornamental fish. Abstrak Pengembangan industri budi daya ikan di Provinsi Aceh perlu dilakukan dengan memberdayakan spesies lokal, namun demikian belum ada informasi yang akurat mengenai status ekonomi ikan-ikan air tawar yang memiliki nilai ekonomis tinggi dan berpotensi untuk dikembangkan sebagai ikan budi daya. Kajian ini bertujuan untuk mengevaluasi potensi ikan-ikan air tawar yang ada di Provinsi Aceh agar dapat dijadikan dasar dalam pemilihan spesies untuk dibudidayakan. Pengambilan contoh melalui eksplorasi dilakukan pada bulan Januari 2008 sampai bulan Juli 2012 di beberapa kawasan dalam Provinsi Aceh. Selama penelitian terkoleksi sebanyak 114spesies ikan, terdiri atas 84 spesies ikan air tawar dan sisanya adalah ikan payau.Diantara ikan air tawar tersebut, sebanyak 40 spesie smerupakan ikan konsumsi dan 14 spe-sies diantaranya bernilai ekonomis tinggi serta berpotensi untuk dibudidayakan, sementara 21 spesies ikan air tawar lainnya memiliki potensi sebagai ikan hias.